REVITALISASI MANAJEMEN PENDIDIKAN ISLAM MELALUI PEMANFAATAN ARTIFICIAL INTELLIGENCE DI STIT DARUL ISHLAH TULANG BAWANG - Khomsinnudin, Khomsinnudin (TA'LIM : Jurnal Studi Pendidikan Islam, 2024)
The Industrial Revolution 4.0 and technological advances, especially Artificial Intelligence (AI), have opened up new opportunities for education to improve the quality of learning and education management. However, Islamic education institutions such as the Darul Ishlah Tulang Bawang College of Tarbiyah are faced with complex challenges such as outdated curriculum and limited resources. Therefore, this study aims to explore the revitalization of Islamic education management through the utilization of AI at the Darul Ishlah Tulang Bawang College of Tarbiyah. This research uses a qualitative approach with a case study method. The data collection techniques used were participatory observation, in-depth interviews, and documentation studies. Participatory observation was conducted to observe the implementation of AI in Islamic education management. In-depth interviews were conducted with relevant parties such as institutional leaders, lecturers, staff, and students. Documentation studies were conducted to analyze related documents such as strategic plans, policies, and reports. The results showed that the implementation of AI in Islamic education management at Darul Ishlah Tulang Bawang College of Tarbiyah has improved the efficiency, personalization, and quality of management and learning processes. However, there are challenges such as resistance to change, data security, and information privacy. Therefore, it is recommended to increase commitment and support from all stakeholders, conduct intensive training and capacity building, ensure data security and adhere to ethical principles, and integrate Islamic values in AI implementation.